2019
DOI: 10.21134/rpcna.2019.06.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Ciberacoso y ansiedad social en adolescentes: una revisión sistemática

Abstract: El ciberacoso ha suscitado el interés de los investigadores en el campo de la psicología. Una de las variables que se ha estudiado en los últimos años en relación con el ciberacoso es la ansiedad social. Sin embargo, no se ha realizado una evaluación global y específica de los resultados en estas dos grandes áreas. El objetivo de este estudio es sintetizar los resultados de los estudios que analizan la asociación entre la ansiedad social y el ciberacoso. Se realizó una revisión sistemática de estudios publicad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
1
3
0
8
Order By: Relevance
“…So, it has been found that during early adolescence, anxiety in the case of social evaluation was the variable that was the most likely to explain being a victim, while anxiety in the face of school punishment was the factor that most likely determined being an aggressor or aggressor-victimized [42]. This reinforces evidence from past studies regarding the bidirectional and positive association between the symptomology of social anxiety and victimization [43][44][45] and the perpetration of cyberbullying [21,34,35,43]. So, adolescents who are less socially skilled in face-to-face interactions may use the digital media to hide from their social fears and feel less inhibited and restricted, potentially increasing their connectivity and participation in the Internet and the social networks, and thereby increasing their probability of engaging in or suffering from aggressive on-line behavior [46].…”
Section: Discussionsupporting
confidence: 70%
“…So, it has been found that during early adolescence, anxiety in the case of social evaluation was the variable that was the most likely to explain being a victim, while anxiety in the face of school punishment was the factor that most likely determined being an aggressor or aggressor-victimized [42]. This reinforces evidence from past studies regarding the bidirectional and positive association between the symptomology of social anxiety and victimization [43][44][45] and the perpetration of cyberbullying [21,34,35,43]. So, adolescents who are less socially skilled in face-to-face interactions may use the digital media to hide from their social fears and feel less inhibited and restricted, potentially increasing their connectivity and participation in the Internet and the social networks, and thereby increasing their probability of engaging in or suffering from aggressive on-line behavior [46].…”
Section: Discussionsupporting
confidence: 70%
“…El segundo objetivo consistió en analizar la asociación de los perfiles de victimización obtenidos con la ansiedad social y la autoestima. Con respecto a la ansiedad social, los resultados obtenidos son congruentes con la hipótesis de partida, sustentada en la evidencia previa (Gómez-Ortiz et al, 2017;Landoll et al, 2015;Pabian, & Vandebosch, 2016;Pontillo et al, 2019;Romera et al, 2016;Ruíz-Martín et al, 2019;Van-den-Eijnden et al, 2014): cuanto mayor es el nivel de victimización, mayor es la ansiedad social, siendo más fuerte la asociación de la ansiedad con la violencia tradicional que con la cybervictimización. En el presente trabajo, el análisis de correlaciones muestra que la ansiedad social correlaciona de manera positiva y estadísticamente significativa tanto con la victimización tradicional como con la cibervictimización.…”
Section: Discusión Y Conclusionesunclassified
“…Los adolescentes que son víctimas tanto de violencia tradicional como de ciberagresiones presentan mayor ansiedad social que los que son principalmente cibervíctimas, pero no difieren de manera estadísticamente significativa con respecto a las victimas de violencia tradicional. Este resultado, además de ser congruente con los obtenidos en los estudios previos revisados (Gómez-Ortiz et al, 2017;Landoll et al, 2015;Pabian, & Vandebosch, 2016;Pontillo et al, 2019;Romera et al, 2016;Ruíz-Martín et al, 2019;Van den Eijnden et al, 2014), es congruente con la hipótesis de Olweus (2012), según la cual la cibervictimización en muchas ocasiones aparece unida a la victimización tradicional y para entenderla se debe analizar en el contexto de un maltrato más amplio, también de tipo presencial. Con respecto a la autoestima, los resultados obtenidos son congruentes con la hipótesis de partida, sustentada por la evidencia previa (Álvarez-García et al, 2019;Chen et al, 2017;Kowalski et al, 2014;Marciano et al, 2020;Tsaousis, 2016;Van Geel et al, 2018): cuanto mayor es el nivel de victimización de los adolescentes, menor es su autoestima, siendo más fuerte esta asociación con la violencia tradicional que con la cibervictimización.…”
Section: Discusión Y Conclusionesunclassified
See 1 more Smart Citation
“…Among the main consequences of being a victim of cyberbullying is the presence of low selfesteem, feelings of loneliness, suicidal thoughts (Kopecký & Szotkowski, 2017), and anxiety (Ruíz-Martín, Bono-Cabré, & Magallón-Neri, 2019). At the same time, victimization is associated with serious psychosocial, affective, and academic problems (Tokunaga, 2010).…”
Section: Introductionmentioning
confidence: 99%